A Multicriteria Application on the Planning of Educational Facilities - Dias Coelho, José (2019)
A multicriteria approach has been used to build a composite index of "lack" of educational facilities, for every municipality in Portugal. The data has been extracted from a relational database containing a wide rage of information on educational facilities, students and teachers. In the paper the structure of the index, the aggregation method and the application on the planning of educational facilities in Portugal are presented.